(untitled) (Baghdad Science Journal, 2022)
The technological development in the field of information and communication has been accompanied by the emergence of security challenges related to the transmission of information. Encryption is a good solution. An encryption process is one of the traditional methods to protect the plain text, by converting it into inarticulate form. Encryption implemented can be occurred by using some substitute techniques, shifting techniques, or mathematical operations. This paper proposed a method with two branches to encrypt text. The first branch is a new mathematical model to create and exchange keys, the proposed key exchange method is the development of Diffie-Hellman. It is a new mathematical operations model to exchange keys based on prime numbers and the possibility of using integer numbers. While the second branch of the proposal is the multi-key encryption algorithm. The current algorithm provides the ability to use more than two keys. Keys can be any kind of integer number (at least the last key is a prime number), not necessarily to be of the same length. The Encryption process is based on converting the text characters to suggested integer numbers, and these numbers are converted to other numbers by using a multilevel mathematical model many times (a multilevel process depending on the number of keys used), while the decryption process is a one-level process using just one key as the main key, while the other keys used as secondary keys. The messages are encoded before encryption (coded by ASCII or any suggested system). The algorithm can use an unlimited number of keys with a very large size (more than 7500 bytes), at least one of them a prime number. Exponentiation is also used for keys to increase complexity. The experiments proved the robustness of the key exchange protocol and the encryption algorithm in addition to the security. Comparing the suggested method with other methods ensures that the suggested method is more secure and flexible and easy to implement.